2009
DOI: 10.1002/pbc.22014
|View full text |Cite
|
Sign up to set email alerts
|

Clear cell sarcoma of the stomach

Abstract: Clear cell sarcoma (CCS) is a high grade soft tissue sarcoma with a distinct molecular profile. Gastrointestinal CCS is very rare and most reported cases are in adults. We describe a 10-year-old female with a 4-month history of anemia who later developed fever, weight loss and abdominal pain. She was subsequently found to have a large infiltrative gastric mass. A diagnosis of CCS was confirmed by molecular and cytogenetic studies. This case illustrates the necessity of a multimodal approach, particularly the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Of 25 cases in the literature that involved assessment for the presence of at least one neuroendocrine marker (including chromogranin-A, synaptophysin, neuron-specific enolase, and CD56) immunohistochemically, 19 (76%) were shown to express at least one of these markers. 1,2,6,[8][9][10]13 In the series by Stockman et al, 13 all cases expressed SOX10 (further supporting evidence of a primitive neural phenotype for CCSLGT) and vimentin. Markers associated with gastrointestinal stromal tumor (GIST)-CD117, DOG1, CD34-are universally negative, and CCSLGT is also negative for desmin, smooth muscle actin, pancytokeratin AE1/AE3 (although 1 of 8 cases has shown focal patchy positivity for Cam5.2), and CD99.…”
Section: Ancillary Studies Immunohistochemistry and Electron Microscopymentioning
confidence: 85%
See 1 more Smart Citation
“…Of 25 cases in the literature that involved assessment for the presence of at least one neuroendocrine marker (including chromogranin-A, synaptophysin, neuron-specific enolase, and CD56) immunohistochemically, 19 (76%) were shown to express at least one of these markers. 1,2,6,[8][9][10]13 In the series by Stockman et al, 13 all cases expressed SOX10 (further supporting evidence of a primitive neural phenotype for CCSLGT) and vimentin. Markers associated with gastrointestinal stromal tumor (GIST)-CD117, DOG1, CD34-are universally negative, and CCSLGT is also negative for desmin, smooth muscle actin, pancytokeratin AE1/AE3 (although 1 of 8 cases has shown focal patchy positivity for Cam5.2), and CD99.…”
Section: Ancillary Studies Immunohistochemistry and Electron Microscopymentioning
confidence: 85%
“…S100 protein positivity has been seen in all 38 CCSLGTs where it was performed, whereas the melanocyte-specific markers were negative in all CCSLGTs studied. 1,2,[5][6][7][8][9][10][11][12][13][14] This is in contrast to conventional-type CCSs occurring in the gastrointestinal tract, most of which are positive for S100 protein as well as melanocyte-specific antigens. There is now increasing evidence that many CCSLGTs also express neuroendocrine markers ( Figure 9).…”
Section: Ancillary Studies Immunohistochemistry and Electron Microscopymentioning
confidence: 99%
“…As many of these tumors have lacked evidence of melanocytic differentiation, and some authors have, therefore, preferred the designation "clear cell sarcoma-like tumor of the gastrointestinal tract" (CCSLTGT). 4,10,13,14,[17][18][19][20][22][23][24][26][27][28][29] A recent study by Antonescu et al 22 showed that the alternative translocation t(2,22)(q32;q12) resulting in a EWS-CREB1 gene fusion occurs preferentially in a group of intestinal CCSs lacking melanocytic differantiation. At the immunophenotypic level, CCSLTGT and CCS share expression of S100 protein, but most, and all with osteoclast-like multinucleated giant cells, differ very significantly in terms of expression of specific melanocytic markers.…”
Section: Discussionmentioning
confidence: 99%
“…To date, 42 cases of gastrointestinal CCS with or without genetic confirmation have been reported. 3,4,11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][32][33][34][35] In this study, we report a case of CCS of gastrointestinal tract with discussion on diagnostic difficulties and the review of literature.…”
Section: Introductionmentioning
confidence: 99%
“…The ileum is the most common site; other reported sites include the stomach, colon, and duodenum. 8,9 In contrast to tumours in the soft parts, tumours in the gastrointestinal tract show both morphological and cytogenetic variations. Although the first morphological variation of the presence of numerous giant cells was noted by Alper and Beckwith, the entity osteoclast-rich giant cell tumour was first described later by Zambrano et al in 2003.…”
Section: Discussionmentioning
confidence: 97%